2014
DOI: 10.1016/j.clinthera.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Flexible-Dose Study of Paliperidone Palmitate in Nonacute But Symptomatic Patients With Schizophrenia Previously Unsuccessfully Treated With Oral Antipsychotic Agents

Abstract: The PALMFlexS study is a pragmatic interventional study compared with randomized controlled trials, conducted in a large, more representative sample of patients with schizophrenia, and designed specifically to mimic real-world clinical situations. The findings support the results from randomized controlled studies. They also demonstrate that a clinically relevant treatment response is possible in patients who are considered to be clinically stable by their physician, supporting the use of flexibly dosed PP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 60 publications
6
38
0
Order By: Relevance
“…Comparable PP1M treatment effects have been observed in other pragmatic studies of symptomatic, exacerbated patients and nonacute patients with schizophrenia (Schreiner et al 2014.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparable PP1M treatment effects have been observed in other pragmatic studies of symptomatic, exacerbated patients and nonacute patients with schizophrenia (Schreiner et al 2014.…”
Section: Discussionsupporting
confidence: 56%
“…Naturalistic and pragmatic studies, such as the current and other recent studies in acute and nonacute patients with schizophrenia (Schreiner et al 2014, provide valuable information in populations more akin to those encountered in routine clinical practice , by allowing patients with relevant comorbidities, co-medications and substance abuse to be included.…”
Section: Discussionmentioning
confidence: 99%
“…At T2, AEs rate (52.1%) was lower than at T1 and consistent with other findings. 29 Further, there was a statistically significant decrease in DOTES mean scores between T1 and T2. This could be explained by the fact that 15 of 59 patients assessed at T1 did not complete the study, including 7 due to AEs.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a recent unblinded 6-month study on patients with schizophrenia treated with paliperidone flexible-dose reported a ≥7% increase in weight in 15.4% of patients. 29 In a recent study on metabolic parameters in patients treated with PP, occurrences of metabolic AEs trended with greater BMI status. 18 Similarly, in our study correlations between higher scores of BMI at baseline and higher levels of triglycerides after 6 and 12 months of PP treatment emerged.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation